Income Volatility, Health and Well-Being - Amélie Adeline; Ismael Choinière Crèvecoeur; Raquel Fonseca; Pierre-Carl Michaud (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2019)
While there is mounting evidence that large income shocks, e.g. in the form of a job loss, may impact health and mortality, little evidence exist on the potential relationship between sustained income volatility, keeping average lifetime income constant, and health. This paper exploits rich survey data on the near-elderly in Canada paired with their administrative tax records to investigate whether a relationship exists between health and well-being on the one hand, and individual-specific volatility of income on the other, decomposing volatility into a permanent and transitory component. Controlling for average lifetime income, we find that a one unit increase in the standard deviation of the permanent component of (log) income experienced over the working life is associated with a lower probability of being in excellent (-23.9%) and very good health (-13.3%), to be satisfied with life (-34.9%), and implies the onset of 1.1 additional mental health issues. Similar results, albeit smaller in size, are found for the transitory component of income. These results have potentially important implications for public policy, as well as, understanding the relationship between the labor market and population health.
Keywords: 330